Attribute substitution and stereotypes about the online Arab public sphere: Predictors of concerns about Internet surveillance in five Arab countries. (May 2019) - Martin, Justin D; Naqvi, S Shageaa; Schoenbach, Klaus
This study examined concerns about Internet surveillance among Internet users in Saudi Arabia, Tunisia, Lebanon, Qatar, and the UAE ( N = 4160). Despite common stereotypes about how variables like gender, youth, income, nationality, and liberal or conservative ideology affect political and cultural attitudes in Arab countries, these indicators were not significant predictors of concerns about online surveillance by governments and companies. Arab nationals reported greater concern about companies monitoring their online activity, while expatriates were more worried about government surveillance. The study uses literature on the attribute substitution heuristic to discuss how people might form stereotypes about large groups.